The Role of Communication in Mount Kelud Eruption Disaster Management Program (Case Study in Ngantru Village, Ngantang District, Malang) - Inggrida, Jedda Ayu; Sukesi, Keppi; Cahyono, Edi Dwi (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2017)
Mount Kelud erupted on February 13, 2014 causing severe damage to public and private facilities in 8 villages in Ngantang, a district in Malang. Post-eruption, the social system was severely damaged, while the local society attempted to survive the disaster. This study aimed to analyze the role of communication in disaster management assisted by the existence of social capital in the aspect of cultivation of crops and agricultural infrastructure. The method used was descriptive qualitative supported by scoring data. Thfindings revealed that the role of communication was to bridge the gap in every aspect of social capital. Besides that, communication functioned as a liaison from every aspect of social capital that was used as disaster management during Mount Kelud eruption The type of communication used was interpersonal communication, where members shared activities and information face-to-face or face-to-face activities on disaster management in Mount Kelud.